Otak dan Akal dalam Ayat-Ayat Neurosains - Fuad Arif Noor (MAGHZA, 2019)
Neuroscience is simply the science that specifically studies Neurons (nerve cells). These nerve cells make up the nervous system, both the central nervous system (brain and spinal cord) and peripheral nerves (31 pairs of spinal nerves and 12 pairs of head nerves). Nerve cells themselves are no longer the smallest unit of nerve cells, the smallest unit of nerve cells (neurons) in synapses, which are the meeting points of two nerve cells that move and forward information (neurotransmitters). At the level of molecular biology, the smallest units are like genes (genetic studies). Generally, neuroscientists focus on nerve cells in the brain. In the Qur'an, the mind has a noble position. It was proven that the word "reason" in the Qur'an is mentioned in large numbers. The word "reason" in the Qur'an is mentioned 49 times. All of them are in the form of 'muilÄri' (a verb that indicates the present and the future), except for the one in the form of 'mÄá¸Ä« (a verb denoting the past). Although the Qur'an does not mention "reason" in its form as "a certain part of humanity" (Ø¬ÙˆÙ‡Ø±Ø§ Ù…Ø³ØªÙ‚Ù„Ø§ ÙÙ‰ Ø§Ù„Ù†ÙØ³), which is the source of birth for all rational actions, but the Qur'an refers to "reason" in its meaning as " activities using reason '(Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù‚Ù„), i.e. calls to use reason as a path to truth (Ø§Ù„ØªØ¹Ù‚Ù„), think (Ø§Ù„ØªÙÙƒØ±), pay attention (Ø§Ù„Ù†Ø¸Ø±), understand and learn (Ø§Ù„ØªÙÙ‚Ù‡), take wisdom and lessons from each event (Ø§Ù„Ø§Ø¹ØªØ¨Ø§Ø±), etc.